Towards a theory of remote area planning and development: community based bird watching tourism in the Arfak Mountains, West Papua - Sharon, Harwood (2008)

(untitled)
This paper examines community based bird watching tourism in the remote village of Siyoubrig, within the Arfak Mountains region of West Papua. There are two levels of planning that influence the intensity of tourism development within the village. One process is undertaken by the destination community and represents the site development planning process and the other is the over arching planning framework that governs development within the region. Remote areas are becoming increasingly popular as tourist destinations that provide for experience based stays. These experiences are related to the attributes of the setting and can be dependent upon the cultural and/or natural values of the destination. This research showed that bird watchers seek experiences that are related to the natural values of the setting as opposed to seeking destinations to participate in the activity of bird watching only. The intensity of development at the destination has the potential to impact upon the quality of the experience sought. Therefore the intensity of development must be commensurate with market demands in order to provide the opportunity for tourists to realise the range of desired experiential outcomes. The challenge for destination communities in remote areas is accessing information about market demands, and balancing the economic aspirations of the community with the perceived market and accessing a formal property system to secure ownership of the land title and the future growth of these enterprises. A formalised land use planning process is dependent upon a well established and accessible property system. Contemporary planning theory applied by western nations does not address the characteristics of remote areas and presumes that a formalised and accessible property system is in place. The paper reviews contemporary planning theory and concludes that a fresh approach to both the theory of planning and planning practices is necessary to enable the delivery of sustainable tourism development outcomes in remote areas.